QGIS Python programming cookbook : master over 170 recipes to help you turn QGIS from a desktop GIS tool into a powerful automated geospatial framework /: master over 170 recipes to help you turn QGIS from a desktop GIS tool into a powerful automated geospatial framework. (2017) - Lawhead, Joel
No abstract available